3D printed hydrogel for articular cartilage regeneration. (15th May 2022) - Yang, Xue; Li, Shuai; Ren, Ya; Qiang, Lei; Liu, Yihao; Wang, Jinwu; Dai, Kerong
Abstract: Tissue engineering is a promising strategy for damaged cartilage tissue repair. Three-dimensional (3D) printed hydrogel exhibits great potential in cartilage tissue engineering for fabricating 3D cell culture scaffolds, owing to its similarity to the extracellular matrix (ECM). Numerous hydrogels have been tested for 3D printing in vitro articular cartilage tissues, including natural and synthetic hydrogels that mimic their in vivo counterparts. The advancement of materials science and 3D printing techniques enables a wide range of fabrication strategies that produce cartilage tissues with delicate structures and on multiple scales. Stimuli-responsive hydrogels, which rely on the external environment to transform to a desired structure or dimension, have likewise been widely studied in tissue engineering. This review summarizes the characteristics, functions, and research conducted on 3D printed hydrogels by categorizing cutting-edge hydrogel materials commonly used in cartilage tissue engineering and their complexes. The challenges and application prospects of hydrogels in cartilage tissue engineering are described. Novel composite hydrogels must be investigated to meet the requirements of native articular cartilage in the aspects of structure, scale, mechanical properties, among others. Combining stimuli-responsive hydrogels with biological scaffolds also shows great potential in various applications, including but not limited to articular cartilage, vascularization, and osteochondral repair.